Optimal energy‐based seismic design of non‐conventional Tuned Mass Damper (TMD) implemented via inter‐story isolation. (20th January 2015) - Reggio, Anna; Angelis, Maurizio De
Summary Inter‐story isolation, an effective strategy for mitigating the seismic risk of both new and existing buildings, has gained more and more interest in recent years as alternative to base isolation, whenever the latter results to be impractical, technically difficult or uneconomic. As suggested by the name, the technique consists in inserting flexible isolators at floor levels other than the base along the height of a multi‐story building, thus realizing a non‐conventional Tuned Mass Damper (TMD). Consistent with this, an optimal design methodology is developed in the present paper with the objective of achieving the global protection of both the structural portions separated by the inter‐story isolation system, that is, the lower portion (below the isolation system) and the isolated upper portion (above the isolation system). The optimization procedure is formulated on the basis of an energy performance criterion that consists in maximizing the ratio between the energy dissipated in the isolation system and the input energy globally transferred to the entire structure. Numerical simulations, performed under natural accelerograms with different frequency content and considering increasing isolation levels along the height of a reference frame structure, are used to investigate the seismic performance of the optimized inter‐story isolation systems. Copyright © 2015 John Wiley & Sons, Ltd.